Economic reforms and khadi and village industries in India - some issues - Swamy, T.L.N. (2005)
This paper presents an analysis of growth, labour absorption and labour efficiency of Khadi and Village industries in the context of economic reforms in India. The results indicate that Khadi and Village industries have shown a declining trend in terms of growth, employment and labour efficiency during the post reforms period (1991.92-2001.02) compared to the pre reforms period (1980.81 to 90.91). - Reproduced.
Keywords: Rural industries - India; Economic reform - India; Economic reform